Acute nitrate poisoning in two cattle - Issi, Mustafa; Gul, Yusuf; Atessahin, Ahmet; Karahan, Izzet (My University, 2008)
This article reports on a nitrate poisoning case in two cattle [a Montafon cross cow at 4 years age (Protocol no 571) and a Simmental cross heifer at 1.5 year age (Protocol no 572)] with suspected acute nitrate poisoning which were brought to the clinic of the Department of Internal Disease, Faculty of Veterinary Medicine, Firat University. The animals were reported to consume feed mixed with ammonium nitrate fertilizer. According to anamnesis, clinical inspection and laboratory analyses, an acute nitrate poisoning was established in both animals. Immediately after diagnosis, a dose of 20 mg kg-1 methylene blue was administered intravenously to decrease methaemoglobinaemia developed after poisoning. Various parameters determined by clinical examinations and laboratory analysis after treatment were observed to return normal values. It is concluded that using methylene blue alone can cure acute nitrate poisoning in cattle. © 2007 Taylor & Francis.
Keywords: Cow; Methaemoglobin; Methylene blue; Nitrate-nitrite poisoning